Ethics and Discussion of Students of the State Islamic University of North Sumatra - Nurfitriansyah, Caesarilda; Zahira, Zalfa; Alfaqih, Irwansyah (Pusdikra-Publishing.com, 2024)
Ethics in the context of higher education encompasses a set of norms and values that govern interactions between students, as well as their relationships with university lecturers and staff. This study aims to explore how ethics are applied in student discussions at UINSU and how it affects the dynamics and quality of academic interaction on campus. The research method used in this paper is a qualitative approach with a focus on the analysis of descriptive data in the form of written texts. The main source of data comes from literature, including reading, understanding, and analyzing various sources of writing and books that are relevant to the problem discussed. This type of study is qualitative, where the data is explained verbally and analyzed without using statistical techniques. In ethical debates, participants think about how they interact with their opponents and spectators in addition to winning or losing. Those who participate in the debate are expected to treat their interlocutors politely and professionally.